Precolumn derivatization LCâMS/MS method for the determination and pharmacokinetic study of glucosamine in human plasma and urine - Min Song; Tai-Jun Hang; Cheng Wang; Lin Yang; Ai-Dong Wen (Elsevier, 2012)
A selective precolumn derivatization liquid chromatographyâtandem mass spectrometric (LCâMS/MS) method for the determination of glucosamine in human plasma and urine has been developed and validated. Glucosamine was derivatized by o-phthalaldehyde/3-mercaptopropionic acid. Chromatographic separation was performed on a Phenomenex ODS column (150Â mmÃ4.6Â mm, 5Â Î¼m) using linear gradient elution by a mobile phase consisting of methanol (A), and an aqueous solution containing 0.2% ammonium acetate and 0.1% formic acid (B) at a flow rate of 1Â mL/min. Tolterodine tartrate was used as the internal standard (IS). With protein precipitation by acetonitrile and then the simple one-step derivatization, a sensitive bio-assay was achieved with the lower limit of quantitation (LLOQ) as low as 12Â ng/mL for plasma. The standard addition calibration curves suitable for clinical sample analysis showed good linearity over the range of 0.012â8.27Â Î¼g/mL in plasma and 1.80â84.1Â Î¼g/mL in urine. The fully validated method has been successfully applied to a pharmacokinetic study of compound glucosamine sulfate dispersible tablets in health Chinese volunteers receiving single oral doses at 500, 1000 and 1500Â mg of glucosamine sulfate, as well as multiple oral doses of 500Â mg t.i.d. for 7 consecutive days. Keywords: Glucosamine, Pharmacokinetics, Precolumn derivatization, LCâMS/MS